ANALISIS DETERMINAN KEPUASAN PENGGUNA SISTEM INFORMASI AKUNTANSI - Ni Putu Lisa Ernawatiningsih; I Putu Edy Arizona (Jurnal Riset Akuntansi, 2022)
Information system user satisfaction can be used as a measure of the success of an information system in a company. In this modern era, companies are always trying to meet the needs of information system users, so as to increase information system user satisfaction. By increasing user satisfaction, it is hoped that performance will be more optimal, which will have an impact on the company. This research was conducted with the aim of knowing the effect of information system quality, perceived user convenience, user participation, and service quality on user satisfaction of accounting information systems at Krisna Holding Company. The sample in this study were 40 employees who used an accounting information system based on a purposive sampling method. The analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that service quality has a positive effect on user satisfaction of accounting information systems; while the quality of information systems, perceived ease of use and user participation do not affect the satisfaction of users of accounting information systems. The implication of this research is that later it can be used as a reference in making policies related to the development of human resource capabilities related to the use of the system and improving the quality of the system to make it more user friendly.